Association between the combined fat mass and fat-free mass index and hypertension: The Tohoku Medical Megabank Community-based Cohort Study. (3rd October 2021) - Takase, Masato; Nakamura, Tomohiro; Tsuchiya, Naho; Kogure, Mana; Itabashi, Fumi; Narita, Akira; Hirata, Takumi; Nakaya, Naoki; Hamanaka, Yohei; Sugawara, Junichi; Suzuki, Kichiya; Fuse, Nobuo; et al.
ABSTRACT: Background: A  higher body fat percentage is associated with hypertension, even in non-obese individuals. The difference in body composition may be related to hypertension. The fat mass index (FMI) and fat-free mass index (FFMI) are proposed indicators of body composition. This study aimed to examine the relationship of a combination of FMI and FFMI with hypertension. Methods: We conducted a cross-sectional study of 5, 058 men and 11, 842 women aged ≥ 20 years in the Miyagi Prefecture, northeastern Japan. The FMI and FFMI were calculated as the fat mass and fat-free mass divided by the height squared, respectively. The indices were classified into quartiles and combined into 16 groups. Hypertension was defined as casual blood pressure ≥ 140/90 mmHg and/or self-reported treatment for hypertension. Multivariable logistic regression models, adjusted for potential confounders, were used to assess the relationship of a combination of FMI and FFMI with hypertension. Results: Higher FMI was associated with hypertension in most of the FFMI subgroups. Similarly, a higher FFMI was associated with hypertension in most of FMI subgroups. For men, the association between FFMI and hypertension in the lowest FMI group was not significant. Conclusions: Reducing the FMI and FFMI may be important in preventing hypertension. For men, the relationship between the FFMI and hypertension in the lowest FMI group might be weak.